Atypical Presentation of Bullous Herpes Zoster in Immunocompetent Host: A Case Report - Jennifer Jesse Limanto; Ina Dia El Em Dama; Benedictus Stefanus (PT Dexa Medica, 2026)
Background: Herpes zoster is a disease caused by reactivation of the varicella-zoster virus, occurring commonly in older adults and rarely in children. In pediatric cases, herpes zoster typically presents with milder symptoms and a shorter duration of illness. However, atypical presentations in otherwise healthy children can pose a diagnostic challenge and warrant careful clinical evaluation. Case: A 14-year-old girl presented with blistering in the left thoracic region, preceded by an episode of fever, followed by the rapid progression of multiple rashes into large bullae, accompanied by stabbing pain. Physical examination revealed multiple vesicles and bullae filled with clear serous fluid on an erythematous base, arranged along the T4 dermatome. A clinical diagnosis of herpes zoster was established. The patient underwent bullae debridement for the giant lesions and was treated with acyclovir, diclofenac sodium, and 2% gentamicin ointment. At follow-up, the lesions showed significant improvement, with no new eruptions, complete pain resolution, and no observed sequelae. Conclusion: Bullous herpes zoster may lead to severe clinical progression even in immunocompetent children. Early diagnosis and appropriate management are essential to prevent morbidity and neurological complications. Therefore, targeted preventive and therapeutic strategies should be considered, especially in the pediatric population.